Bis-triazóis funcionalizados como modificantes de eletrodos para determinação voltamétrica de metais - Freire, Brenda Rafaela Lima (2024)
The detection of heavy metals in solution is necessary due to their toxic properties and bioaccumulation potential, which can be harmful to living organisms. Chemically modified electrodes have been widely used as an alternative in the detection of heavy metal ions, aiming for improved selectivity resulting from specific interactions with these analytes. Therefore, ligands derived from bistriazolic compounds emerge as new materials capable of interacting with metallic ions, potentially enhancing the detectability of the electrode. In this context, this work aims to obtain electrodes modified with ligands derived from bis-triazoles (BT) for the detection of metals such as Cd, Cr, Fe, and Pb, along with the development of a method for detecting lead(II) ions. The bis-triazoles were characterized using spectroscopic, spectrometric, and electrochemical techniques. An evaluation of the current intensities obtained for lead(II), cadmium(II), iron(II), and chromium(VI) ions was performed by comparing each modified electrode (BTE) to the unmodified carbon paste electrode (CPE). A correlation was observed between the ionic radius of the analyzed metals, their intermolecular interactions with the modifiers, and the obtained electrochemical response. Additionally, a method for the determination of lead(II) ions was developed using differential pulse voltammetry (DPV), where the modified electrode EBT/A (A = 1,3-bis(4-ethyl-1H-1,2,3-triazol-1-yl)propan-2-one) demonstrated remarkable detectability for Pb2+. Optimizations of the scan medium parameters and the DPV technique showed a significant increase in the analytical signal current for Pb2+. An analytical curve was obtained, and the developed method achieved a detection limit of 0.10 nmol L-1. The method was applied to quantify the analyte in tap water, river water, and firearm discharge residue samples with recovery values ranging from 87.8% to 118.46%,highlighting the reliability and precision of the developed EBT/A method.